Digital marketing strategy of Waroeng Steak & Shake in building brand and millennial customer loyalty - Agus wawan; Taryono; Sutrisno (International Enterprise Integration Association, 2026)
This study aims to analyze the influence of digital marketing strategy on brand equity and millennial customer loyalty at Waroeng Steak & Shake in the increasingly competitive culinary industry. It also contributes to marketing literature by integrating digital marketing strategy and brand equity as key determinants of sustainable millennial loyalty in the context of a local culinary brand in Indonesia. A quantitative research design was employed using primary data collected from 195 millennial customers who had made purchases within the last three months. Data were gathered through structured questionnaires and analyzed using multiple linear regression with SPSS version 25, including descriptive statistics, validity and reliability testing, classical assumption tests, and hypothesis testing. The results indicate that digital marketing strategy has a positive and statistically significant effect on brand equity (β = 0.512; p < 0.001) and customer loyalty (β = 0.437; p < 0.001). Furthermore, brand equity significantly influences loyalty (β = 0.468; p < 0.001) and partially mediates the relationship between digital marketing and loyalty. The coefficient of determination shows that the model explains 63.4% of the variance in loyalty. These findings highlight the strategic synergy between digital engagement and brand value in strengthening emotional attachment and long-term relationships. However, the study is limited to a single brand and a cross-sectional design; future research should include broader contexts and additional variables.